1997
DOI: 10.1002/ange.19971091234
|View full text |Cite
|
Sign up to set email alerts
|

1,2‐Didehydrobenzol: ein gespanntes Alkin oder ein Cumulen? — NMR‐spektroskopische Charakterisierung in einem molekularen Container

Abstract: Rechtzeitig zum 100. Geburtstag von Georg Wittig konnte das 1H‐ und das 13C‐NMR‐Spektrum von 1,2‐Didehydrobenzol 1 in Lösung gemessen werden. 1 wurde photochemisch in der Cavität des Hemicarceranden 2 aus incarceriertem Benzocyclobutendion in zwei Schritten über den Benzocyclopropenon‐Hemicarceplex hergestellt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
3

Year Published

1998
1998
2012
2012

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(18 citation statements)
references
References 35 publications
0
15
0
3
Order By: Relevance
“…Die thermochemischen Eigenschaften der Singulett‐ und Triplett‐Zustände wurden bestimmt,8, 9 und auch IR‐spektroskopische Untersuchungen an den ortho‐ 10 und meta ‐Isomeren11 wurden durchgeführt. Die Struktur von ortho ‐Benz‐in wurde NMR‐spektroskopisch analysiert 12. Somit steht nur noch für das para ‐Isomer 1 ‐ p eine genaue spektroskopische Charakterisierung aus, obwohl hierzu Daten in begrenztem Umfang vorliegen 9…”
Section: Methodsunclassified
“…Die thermochemischen Eigenschaften der Singulett‐ und Triplett‐Zustände wurden bestimmt,8, 9 und auch IR‐spektroskopische Untersuchungen an den ortho‐ 10 und meta ‐Isomeren11 wurden durchgeführt. Die Struktur von ortho ‐Benz‐in wurde NMR‐spektroskopisch analysiert 12. Somit steht nur noch für das para ‐Isomer 1 ‐ p eine genaue spektroskopische Charakterisierung aus, obwohl hierzu Daten in begrenztem Umfang vorliegen 9…”
Section: Methodsunclassified
“…Sodium hydride (85 % in oil, 0.56 g, 20.0 mmol) was added to tricarbonyl(η 6 -2,5-dimethoxyphenol)chromium(0) (12,4.01 g, 13.9 mmol) in CH 2 Cl 2 (50 mL). After the mixture had been cooled to -78°C, triflic anhydride (2.4 mL, 14.2 mmol) was added to the stirred mixture.…”
Section: Tricarbonyl[η 6 -(25-dimethoxyphenyl Triflate)]chromium(0) mentioning
confidence: 99%
“…Arynes [1,2] (dehydrobenzenes) are valuable intermediates combining important aspects of theory, [3] spectroscopy, [4] and applications for the synthesis of natural [5,6] and unnatural products. [7][8][9][10] Methods for the generation of 1,2-dehydrobenzene involve elimination from aryl anions, aryl cations, aryl radicals, and zwitterions, as well as fragmentation reactions.…”
Section: Introductionmentioning
confidence: 99%
“…(© Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2005) active intermediates have been generated and stabilized by preventing their dimerization or the reaction with bulkphase reactants that are too large to enter the inner phase. [6][7][8][9][10][11][12][13][14][15][16][17] Encapsulation has also been applied to investigate fundamental aspects of electron and energy transfer processes, [18][19][20][21][22] to change and control the rate and regiochemistry of bimolecular reactions, [23][24][25][26][27][28][29][30][31][32][33] to amplify reactions, [34] and to alter the position of chemical equilibria. [35] Recently, Rebek and co-workers and Fujita and coworkers showed that Diels-Alder reactions and photochemical [2+2] additions are strongly accelerated in the presence of a self-assembled capsule or coordination cage.…”
Section: Introductionmentioning
confidence: 99%